2019
DOI: 10.1007/s10433-019-00508-y
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of elderly Austrians towards new technologies: communication and entertainment versus health and support use

Abstract: We use data from SHARE (The Survey of Health, Ageing and Retirement in Europe) in Austria to investigate attitudes towards new technologies in information and communication technology. The technologies can significantly facilitate the daily lives of an ageing population. In Austria, in wave 6 in 2015, an additional paper-and-pencil questionnaire was implemented which asked details about attitudes towards different technological innovations. From these questions, we develop a binary attitude score which indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 22 publications
1
12
1
Order By: Relevance
“…Providing the elderly with places to play chess and mahjong in the community. [27,33,[37][38][39] 2. Drama, singing and dancing…”
Section: Chess and Mahjongmentioning
confidence: 99%
“…Providing the elderly with places to play chess and mahjong in the community. [27,33,[37][38][39] 2. Drama, singing and dancing…”
Section: Chess and Mahjongmentioning
confidence: 99%
“…Still within this group both the frequency of use of digital communications and their type may vary. Previous studies have shown that among individuals aged 50 and over, younger age, being men, higher education, and more economic resources are associated with higher levels of digital literacy and with more regular use of the Internet (Halmdienst et al 2019 ; van Deursen and van Dijk 2015 ), although these differences have somewhat reduced over time (Huxhold et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, both the Polish study [2] and our current study indicate that the female respondents were dominating, which might be connected with a longer life expectancy of females and more frequent report to the doctor for advice. In addition, the reason might be the fact that females are more positive about the devices which include health or support value, while males appreciate communication and entertainment devices [16]. The study findings showed that there were significant differences between the e-Health supporters and the non-supporters.…”
Section: Discussionmentioning
confidence: 82%